Modern family. The complete first season [videorecording (DVD)] - O'Neill, Ed, 1946-; Vergara, Sofía, 1972-; Bowen, Julie; Burrell, Ty, 1967-; Ferguson, Jesse Tyler (20th Century Fox Home Entertainment, 2010)
Modern Family takes a refreshing and funny view of what it means to raise a family in this hectic day and age. Multicultural relationships, adoption, and same-sex marriage are just a few of the timely issues faced by the show's three wildly-diverse broods. No matter the size or shape, family always comes first in this hilariously 'modern' look at life, love, and laughter.